Influence of Occupational Health and Safety Risk On Human Resources on Project Continuity (Case Study: Muhammadiyah University Education Hospital Semarang) - Ariyanto, Ariyanto; Wakit, Ahmat; Luthfi, Ahmad (CIVED, 2023)
This type of research uses a quantitative descriptive approach, namely describing and analyzing the problems found. Quantitative research is based on primary data and secondary data. This research aims to determine the positive influences between: (1). Employee performance influences work safety. (2). Worker awareness influences work safety. (3). Workers' health influences work safety. On the Semarang Muhammadiyah University Teaching Hospital Construction Project. The results of this research show that work safety has a positive and significant effect of 89.9% on employee performance, and worker health on project sustainability. With the help of SmartPLS3.0 software